BOOK REVIEW: CRITICAL NOTES ON IMAJINASI SOSIOLOGI: PEMBANGUNAN SOSIETAL - B.J. Sujibto (Jurnal Sosiologi Reflektif, 2022)
The essay is to examine a book entitled Imajinasi Sosiologi: Pembangunan Sosietal by underlining two significant elements to critically read and debate some problematic theories and other explanations. Firstly, concerning sociological theories and social theories in general in which the author paid attention; secondly, the author’s discipline of implementing the theories based on the data and contextual basis of Indonesian society. I am concerned a lot with the theoretical problems of the book and how the author explained sociological theories since they are used as a tool to analyse current topics particularly of ‘societal’ development (with an apostrophe to indicate a new term for Indonesian society of either academic or popular usage). Apart from many typos and lack of references, the review found at least two problems to argue: first is about conceptual and theoretical problems and lexical inconsistencies including the major theory of sociological imagination used as a title of the book, and second is a failure to exercise the care that reference and citation must be rigorously taken into consideration.Esai ini mengkaji buku berjudul Imajinasi Sosiologi: Pembangunan Sosietal dengan menggarisbawahi dua hal penting yang bisa dievaluasi dan dikritik. Pertama, tentang teori-teori sosiologi dan teori-teori sosial lainnya yang menjadi fokus penulis; kedua, kedisiplinan penulis dalam menerapkan teori berdasarkan data dan landasan kontekstual masyarakat Indonesia. Saya menaruh perhatian serius dalam masalah teori dalam buku ini dan bagaimana penulis menjelaskan teori sosiologi karena teori-teori tersebut digunakan sebagai alat untuk menganalisis topik khususnya tentang pembangunan ‘sosietal’ (dengan apostrof untuk menunjukkan istilah baru untuk masyarakat Indonesia baik penggunaan akademik atau populer). Terlepas dari banyak kesalahan ketik dan kurangnya penyediaan sitasi dan referensi, ulasan ini menemukan setidaknya dua masalah untuk diperdebatkan: pertama tentang masalah konsep dan teori dan inkonsistensi leksikal termasuk teori utama imajinasi sosiologis yang digunakan sebagai judul buku, dan kedua adalah kegagalan untuk berhati-hati bahwa referensi dan kutipan harus benar-benar dipertimbangkan dalam karya akademik.